[Quaestiones super libros posteriorum Aristotelis]. - Albertus, de Saxonia, -1390. (Tufts University. Tisch Library., 2016)
1 online resource (48 leaves); Title supplied by cataloger.; Layout: Written in 2 columns; ruled.; Decoration: Red initials and headings.; Binding: Parchment-covered hardback with leather cord in corners; ruling and letterforms visible on reverse of parchment.; Origin: Written in Italy, likely Tuscany, perhaps Siena.; Shelfmark: Ms. 14.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2016.; Indexed in: Hain,580; Tisch In-House Digitization 2016-10-25